2013
DOI: 10.3389/fphys.2013.00146
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning of heat production in growing pigs as a tool to improve the determination of efficiency of energy utilization

Abstract: In growing pigs, the feed cost accounts for more than 60% of total production costs. The determination of efficiency of energy utilization through calorimetry measurements is of importance to sustain suitable feeding practice. The objective of this paper is to describe a methodology to correct daily heat production (HP) obtained from measurements in respiration chamber for the difference in energy expenditure related to physical activity between animals. The calculation is based on a preliminary published appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 35 publications
0
29
0
1
Order By: Relevance
“…However, it is difficult to discriminate between IC and growth effect. Comparing with the literature, it can be hypothesized that PD was likely increased due to growth, but not affected by IC, as Labussière et al (2013) showed similar PD in IC and EM pigs 5 weeks after V2 (and superior to barrows). On the other hand, LD seems to be increased not only with growth, but also due to IC.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…However, it is difficult to discriminate between IC and growth effect. Comparing with the literature, it can be hypothesized that PD was likely increased due to growth, but not affected by IC, as Labussière et al (2013) showed similar PD in IC and EM pigs 5 weeks after V2 (and superior to barrows). On the other hand, LD seems to be increased not only with growth, but also due to IC.…”
Section: Discussionmentioning
confidence: 61%
“…A numerical decrease in fasting HP was even noted, which illustrates the important changes in the physiology and metabolism due to IC. Higher body fatness (van Milgen et al, 1998) and changed hormonal status after IC (castrate v. male, Labussière et al, 2013) have both been associated with decreased basal metabolic rate. In the present study, there was also no effect of IC/growth on total thermic effect of feeding (as % ME).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…time of intake and ingested quantity) and physical characteristics of the gas in the chamber were used to calculate the components of HP according to the modeling approach of van Milgen et al (1997). Parameters of the differential equations for gas concentrations in the respiration chamber involved in the model were estimated using the R software (Labussière et al, 2013). The HP due to physical activity (AHP), HP due to feed intake (short-term thermic effect of feeding, TEF s ) and HP due to resting metabolism (RHP) were calculated from respective volumes of O 2 consumption and CO 2 production according to the Brouwer equation (Brouwer, 1965), excluding urinary N losses and CH 4 production.…”
Section: Calculationsmentioning
confidence: 99%
“…Dr Sarafian (from the laboratory of Dr Dulloo) described a new approach to perform standardized tests for assessing human variability in the energy cost of low-intensity isometric work that is comparable to daily life activities (Sarafian et al, 2013). Etienne Labussière described the method used in his laboratory to deal with this question in large farm animals such as white pigs (Labussiere et al, 2013), and Jan B van Klinken described the most advanced procedures for rats and mice and compared their robustness in relation to the frequency of data acquisition and quality of the activity signal (van Klinken et al, 2013). In his review, John Speakman developed an extensive section on physical activity in which he discussed the various issues related to this question (including treadmill running) and surveyed the most significant published works (Speakman, 2013).…”
mentioning
confidence: 99%